Efektivitas Full Body Stretching dan Edukasi Manual Handling Digital terhadap Keluhan Musculoskeletal Disorders Pekerja Yantek - Rosalinda, Nadia; Sulistyorini, Anita; Marji, Marji; Supriyadi, Supriyadi; Tama, Tika Dwi (UI Scholars Hub, 2025)
Occupational Diseases (PAK) in the form of pain complaints in the skeletal system that cause the work process are called Musculoskeletal Disorders (MSDs). PT. PLN Yantek workers are at risk of experiencing MSDs complaints because the work is done manually and the work posture is less ergonomic. This study aimed to analyze the effect of implementing full-body stretch and digital-based manual handling education and to assess its effectiveness on MSDs. The study used a quasi-experimental method with a one-group pretest-posttest design involving 26 Yantek workers. The intervention was given at 10 meetings, MSDs complaints were measured using the Nordic Body Map questionnaire and analyzed using a paired sample t-test with a significance of α = 0.005. The study's results on the full body stretch variable and digital-based manual handling education in the experimental group showed a p-value of 0.000, which means there are differences in MSDs complaints before and after the intervention. The full-body stretch intervention results showed a mean difference of 13.27, while the digital-based manual handling education intervention showed a mean difference of 10.58. Therefore, both interventions have the same effect in reducing MSDs complaints, but whole-body stretching showed greater effectiveness. Keywords: musculoskeletal disorders (MSDs), full body stretching, digital-based manual handling education